Monkeypox outbreak in Madrid (Spain): Clinical and virological aspects. Issue 4 (October 2022) - Orviz, Eva; Negredo, Anabel; Ayerdi, Oskar; Vázquez, Ana; Muñoz-Gomez, Ana; Monzón, Sara; Clavo, Petunia; Zaballos, Angel; Vera, Mar; Sánchez, Patricia; Cabello, Noemi; Jiménez, Pilar; et al.
Highlights: Throughout May 2022, an outbreak of monkeypox disease has been described in Europe, mostly in MSM. The most frequent symptoms are vesicular-umbilicated and pseudopustular skin lesions, asthenia, and fever. The location of the lesions in the genital or perianal area was related to the role in sexual intercourse. The prognosis of the disease is good, with self-limited skin lesions without serious complications. Sequencing analysis indicated this virus belongs to the western African clade and are direct descendant of viruses previously detected in Nigeria, the UK, Singapore, and Israel in 2017–2018. Summary: Background: Monkeypox is the most prevalent Orthopoxvirus zoonosis infection since the eradication of smallpox. The current multi-country outbreak involves five WHO regions affecting mainly Europe. Accurate clinical and virological aspects of the disease outside endemic areas are needed. Methods: We performed an observational study of cases diagnosed in Madrid (Spain) (May/June 2022). Confirmation from vesicular lesions swabs, Orthopoxvirus real-time PCR, sequencing, phylogenetic analysis, and direct detection by Electron microscopy was performed. In addition, a structured epidemiological questionnaire was completed systematically to gather sociodemographic, clinical, and behavioral data from all confirmed cases. Findings: We extracted data from 48 patients, all cisgender men. The median age was 35 years (IQR 29 – 44), and 87.5% were MSM. The most prevalent symptoms were the presence of vesicular-umbilicated and pseudo-pustular skin lesions (93.8%), asthenia (66.6%), and fever (52.1%). In addition, the location of the lesions in the genital or perianal area was related to the role in sexual intercourse ( p <0.001). Sequencing analysis indicated the virus circulating in Spain belongs to the western African clade. Like the other European cases in the outbreak, the Spanish isolates are a direct descendant of viruses previously detected in Nigeria, the UK, Singapore, and Israel in 2017–2018. Conclusions: Monkeypox is an emerging infectious disease in Europe where community transmission is reported, mainly in MSM. The first symptom was skin lesions instead of classical fever and rash. The disease follows a self-limited course, and there have been no cases with a serious presentation or severe complications.